An Interactive Web-Based Tool For Teaching Computer Programming - Abdel-Raouf, Amal (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2016)
Lab time dedicated to programming practice in most schools is typically not sufficient for students to succeed as professional programmers. In this paper, we introduce an interactive tool for teaching computer programming. The tool can be used outside the classroom as it is web-based, can be easily integrated with any management learning environment such as BlackBoard, and provides better opportunities for distance learning and online education programs. The tool engages students as active learners and considers student learning styles to effectively improve the learning process. Our experimental study shows that using our tool significantly increased the achievement percentage of our class learning outcomes.